Slow boat to China and other stories - Ng, Kim Chew, 1967- (Modern Chinese literature from Taiwan., 2016)
"Dream and Swine and Aurora," "Deep in the Rubber Forest," "Fish Bones," "Allah's Will," "Monkey Butts, Fire, and Dangerous Things"--Ng Kim Chew's stories are raw, rural, and rich with the traditions of his native Malaysia. They are also full of humor and spirit, demonstrating a deep appreciation for human ingenuity in the face of poverty, oppression, and exile. Ng creatively captures the riot of cultures that roughly coexist on the Malay Peninsula and its surrounding archipelago. Their interplay is heightened by the encroaching forces of globalization, which bring new opportunities for cultural experimentation, but also an added dimension of alienation. In prose that is intimate and atmospheric, these sensitively crafted, resonant stories depict the struggles of individuals torn between their ancestral and adoptive homes, communities pressured by violence, and minority Malaysian Chinese in dynamic tension with the Islamic Malay majority. Told through relatable characters, Ng's tales show why he has become a leading Malaysian writer of Chinese fiction, representing in mood, voice, and rhythm the dislocation of a people and a country in transition.